MANAJEMEN PEMANFAATAN SARANA DAN PRASARANA PEMBELAJARAN - Erni Susilawati (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2020)
This study aimed at finding out management of the use of facilities and infrastructure in learning, obstacles and the solutions in Elementary School of 25 Betung. This research used a qualitative method. Subject in this study was the principal, teachers, infrastructure coordinator, school committee and supervisor. Technique of collecting data employed observation, interview and documentation. The technique of data validity used triangulation of methods and sources. Data analysis techniques used interactive model. The management of learning facilities and infrastructure is utilized through planning, implementing and controlling facilities and infrastructure. The obstacles are the storage area requires funds for expansion and repair, and a lack of administrative personnel, especially for the management of facilities and infrastructure. Solving budget problems by optimizing the limited personnel is to be more observant in determining the priority scale according to the existing budget, then involving existing personnel in formal courses or training.